Economic Valuation of Biodiversity Services in Tanjung Puting National Park Using the Willingness to Pay Approach - Candra Wulan Ika Purnomo (Journal Informatic, Education and Management (JIEM), 2026)
Biodiversity constitutes a fundamental pillar of sustainable development by providing ecological, social, and economic benefits. National parks play a crucial role in conserving biodiversity while simultaneously delivering ecosystem services that support human well-being. However, many of these services are non-market in nature and are often undervalued in policy-making processes. This study aims to estimate the economic value of biodiversity services in Tanjung Puting National Park using the Willingness to Pay (WTP) approach and to analyze socio-demographic factors influencing visitors’ willingness to contribute to conservation efforts. Data were collected through a structured survey administered to visitors and local communities. The results indicate that respondents demonstrate a positive willingness to pay for biodiversity conservation, with income, education level, and environmental perception significantly influencing WTP values. These findings provide empirical evidence to support conservation financing strategies and sustainable management policies for national parks.